Histological grading based on poorly differentiated clusters is predictive of tumour response and clinical outcome in rectal carcinoma treated with neoadjuvant chemoradiotherapy. Issue 3 (23rd June 2017) - Reggiani Bonetti, Luca; Lionti, Simona; Domati, Federica; Pagliani, Giuliana; Mattioli, Elisabetta; Barresi, Valeria
Abstract : Aims: The clinical outcome of patients with locally advanced rectal cancer who undergo neoadjuvant chemoradiotherapy (CRT) is influenced by the tumour response to treatment, which is reflected by tumour regression grade and post‐treatment (y) TNM stage. Little is known about the prognostic value of pretreatment histopathological features of the tumour that may be useful to discriminate potential non‐responders and to design tailored therapeutic strategies. In this study, we aimed to investigate the prognostic role of poorly differentiated clusters (PDCs) of neoplastic cells in pretreatment biopsies of patients with rectal cancer treated with neoadjuvant CRT. Methods and results: Grading based on PDC counting was retrospectively applied to 204 pretreatment endoscopic biopsies of rectal carcinomas from patients treated with neoadjuvant CRT and surgery. Interobserver agreement in the assessment of PDC grade was good. High PDC grade was significantly associated with high yT stage ( P  = 0.044), yM+ status ( P  = 0.0004), and unchanged TNM stage or TNM upstaging ( P  = 0.032). In addition, high PDC grade was a significant and independent prognostic factor for cancer‐specific survival. Conclusions: PDC grade may be assessed in preoperative biopsies of rectal cancer with good reproducibility. High PDC grade in a pretreatment tumour is significantly associated with a poor response to therapy. Hence, we suggest that PDC grading might be used as a significant predictive and prognostic factor in patients with locally advanced rectal cancer who are treated with neoadjuvant CRT, and to identify high‐risk patients who need surgery and adjuvant chemotherapy.